IoT-Based Smart Fire Alarm Navigation System - Mokhtar'udin, Muhammad Darwish; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2024)
This work aims to solve the problems caused by negligence and a delayed reaction in fire-related accidents by creating an IoT-Based Smart Fire Alarm Navigation System. The suggested system integrates a few sensors, such as temperature, gas, and GPS modules, using Arduino technology to identify and address fire dangers in residential structures. The Arduino IDE software is used to code the Arduino Mega platform, which is the system's central component and allows smooth communication between different parts. The primary goals of this study are to establish an alert system that alerts both firemen and inhabitants in real-time, as well as the development of an IoT-based Smart Fire Alarm Navigation System and an assessment of its functioning performance. Users may get warnings and incident data via cell phones. The system's utilization of Wi-Fi modules guarantees remote monitoring and notification capabilities. The study emphasizes the significance of prompt and well-informed reactions to fire occurrences to minimize the spread of flames and lower related losses. Additionally, to facilitate communication with the fire department, the system automatically logs important details about fire occurrences, including the date, time, and location. This data is then kept in an online cloud storage service. To sum up, this research advances the technology for home fire safety and provides a workable and effective way to counteract the problems caused by neglect and late reporting. By reducing the effect of home fires on lives and property, deploying the IoT-based Smart Fire Alarm Navigation System can significantly improve response times.